2019
DOI: 10.1097/ta.0000000000002398
|View full text |Cite
|
Sign up to set email alerts
|

Female platelets have distinct functional activity compared with male platelets: Implications in transfusion practice and treatment of trauma-induced coagulopathy

Abstract: BACKGROUND Females are hypercoagulable and have survival benefit in trauma-induced coagulopathy (TIC). The mechanism for this sex-specific hypercoagulability is unknown. Platelets and platelet function are central in providing hemostatic potential and are the largest contributor to clot strength. Ligands (adenosine diphosphate [ADP] and platelet-activating factor [PAF]) bind distinct platelet receptors to potentiate activation and aggregation. We hypothesize that female platelets have a differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 42 publications
1
50
0
1
Order By: Relevance
“…Additionally, estradiol pretreatment feminizes male platelets. 31 These hormonal effects may play a role in the performance of platelets in trauma-induced coagulopathy and may contribute to sex-specific outcomes in severe trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, estradiol pretreatment feminizes male platelets. 31 These hormonal effects may play a role in the performance of platelets in trauma-induced coagulopathy and may contribute to sex-specific outcomes in severe trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Male and female platelets have a differential response to ligand-induced activation, and female platelets show an increased activation potential. Male platelets pretreatment estradiol displayed approximate female platelet activation induced by platelet-activating factor [ 42 ]. A case-control study demonstrated women oral contraceptives increased the risk of venous thrombosis, and showed a positive association with oestrogen dose [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Lastly, and of great clinical significance, Colman et al reported gender differences in TIC, with female platelets having increased aggregation and activation potential compared with platelets from males. 58 The authors further suggested that estradiol may serve as a possible therapeutic adjunct in treating eTIC. 58 These findings raise many new questions on the effect of gender on the relative contributions of platelets and fibrinogen to clot formation in trauma patients, which may be sought using a variety of methods including ROTEM, TEG, rapid-kinetic monitoring, X-ray crystallography, nuclear magnetic resonance, and electron microscopy.…”
Section: Platelet and Fibrinogen Contributions To Early Ticmentioning
confidence: 99%
“…58 The authors further suggested that estradiol may serve as a possible therapeutic adjunct in treating eTIC. 58 These findings raise many new questions on the effect of gender on the relative contributions of platelets and fibrinogen to clot formation in trauma patients, which may be sought using a variety of methods including ROTEM, TEG, rapid-kinetic monitoring, X-ray crystallography, nuclear magnetic resonance, and electron microscopy. [59][60][61] In the clinical environment, this new information may help guide which resuscitation protocol and blood product(s) is best suited for males and females following trauma.…”
Section: Platelet and Fibrinogen Contributions To Early Ticmentioning
confidence: 99%